The Association Between Alpha-1 Adrenergic Receptor Antagonists and In-Hospital Mortality From COVID-19 - Rose, Liam; Graham, Laura; Koenecke, Allison; Powell, Michael; Xiong, Ruoxuan; Shen, Zhu; Mench, Brett; Kinzler, Kenneth W.; Bettegowda, Chetan; Vogelstein, Bert; Athey, Susan; Vogelstein, Joshua T.; et al. (Frontiers in Medicine, 2021)
Effective therapies for coronavirus disease 2019 (COVID-19) are urgently needed, and preclinical data suggest alpha-1 adrenergic receptor antagonists (⍺1-AR antagonists) may be effective in reducing mortality related to hyperinflammation. Using a retrospective cohort design with patients in the Department of Veterans Affairs healthcare system, we use doubly robust regression and matching to estimate the association between use of ⍺1-AR antagonists at time of hospitalization and likelihood of death due to COVID-19 during an inpatient stay. Having an active prescription for an ⍺1-AR antagonist (tamsulosin, silodosin, prazosin, terazosin, doxazosin, or alfuzosin) at the time of admission had a significant negative association with in-hospital mortality (relative risk reduction 14%; odds ratio 0.75; 95% CI 0.66 to 0.86; p < 0.001). These effects were also found in an expanded cohort of suspected COVID-19 patients, supporting the need for clinical trials.